Bi-modal reprogramming of cell cycle by MiRNA-4673 amplifies human neurogenic capacity. Issue 8 (18th April 2019) - Farahani, Ramin; Rezaei-Lotfi, Saba; Simonian, Mary; Hunter, Neil
ABSTRACT: Molecular mechanisms that inform heterochronic adaptations of neurogenesis in Homo sapiens remain largely unknown. Here, we uncover a signature in the cell cycle that amplifies the proliferative capacity of human neural progenitors by input from microRNA4673 encoded in Notch-1. The miRNA instructs bimodal reprogramming of the cell cycle, leading to initial synchronization of neural precursors at the G0 phase of the cell cycle followed by accelerated progression through interphase. The key event in G0 synchronization is transient inhibition by miR4673 of cyclin-dependent kinase-18, a member of an ancient family of cyclins that license M–G1 transition. In parallel, autophagic degradation of p53/p21 and transcriptional silencing of XRCC3/BRCA2 relax G1/S cell cycle checkpoint and accelerate interphase by ≈2.8-fold. The resultant reprogrammed cell cycle amplifies the proliferative capacity and delays the differentiation of human neural progenitors.